Confucian Belief-System Towards Political Well-Being: The Foundation of Legitimacy in Representative Government - Kwanhu, Lee (Journal of Dharma, 2025)
In the legitimation of government, the beliefs of the people are essential. A belief system, distinct from authority, government, or power, is a collection of shared convictions. Without the people’s recognition of the political relationship grounded in these belief systems, government becomes untenable. Since every government must secure political legitimacy, a belief system rooted in culture, morality, and religion is necessary. Confucianism, from its inception, serves as such a belief system, bridging religion, moral principles, and social-political norms. Within Confucianism, the right to govern is granted by the ‘Mandate of Heaven.’ Even today, many South Korean politicians often refer to Mencius’ words during election campaigns: "The mind of Heaven is the mind of the people". The idea that "Heaven only hears the voice of the people" reflects the sentiment of limited government within Korea’s representative system.